“Ordinance No. 10: An Ordinance Prohibiting the Carrying of Concealed Deadly Weapons, and Fixing the Penalty Therefor.” The Lompoc Record, August 21, 1888, p. 2. Volume 14, Number 23 - (:unkn) unknown (General Publisher, 1888)
Prohibited the concealed carry of any pistol, revolver, dirk, stiletto, or other dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED